Optimizing Community Reading Parks “Hikari Library” through the Implementation of a Library Management System: Optimalisasi Taman Baca Masyarakat (TBM) Melalui Implementasi Library Management System di Taman Baca Masyarakat “Perpustakaan Hikari” - Nasution, Arbi Haza; Monika, Winda (Institut Riset dan Publikasi Indonesia, 2024)
The optimization of Community Reading Park (TBM) is one solution to stimulate and develop the reading interest of the Indonesian community, aiming to create an educated Indonesian society with a decent income to accelerate the achievement of Sustainable Development Goals (SDGs) 2030. The TBM that partners with this Community Service (P2M) activity is the Hikari Library located in RW.13 / RT.04 Alamanda II Housing precisely on Taman Karya Ujung Street, Pekanbaru City. This TBM has been established since 2019. However, the management and utilization of this library have not been optimal. The hundreds of collections owned are not well-documented, and a retrieval system for the collections has not been implemented. Moreover, the collection service system is entirely manual and sometimes not documented, leading to many borrowed collections being lost and not returned. The proposed solution to the partner is the implementation of a library information system management to assist in the proper governance of the library. Based on pre-tests and post-tests distributed to librarians, it shows an improvement in understanding by 7,49%, and with a satisfaction level of 93,8 %. This Community Service program is conducted in several stages, including 1) pre-activity; 2) implementation; and 3) evaluation.